SISCOND : um sistema para gestão de condomínios - Nunes, Lucas dos Santos (2019)
The administration of a condominium is not an easy task, since it is necessary to add a sequence of information, requisitions and specificities. Management constantly fixes problems related to the most different issues such as security, that is, to ensure that the condominium is using unauthorized access, and that facts are resolved before they demonstrate an exact risk to condominium owners. Other challenges for the administration are solutions for communication and conflict resolution, where all authorized persons can give suggestions, comment or keep complaints timely, since the presence in the assemblies is gradually becoming small. Since virtually everything can be stored nowadays, it is easier to obtain a decision, in which it is simpler to guarantee the syndicate's dialogue with the residents. Other obstacles are the reserves of spaces, such as the party room, the pool and the barbecue, the default situations, the control and management of the works, and the inspection of vehicles, condominiums or visitors. In the context of home automation, the use of the Internet of Things (IoT) and Artificial Intelligence (AI) has indicated the variety of intelligent instruments with efficient processing, management, dialogue, interactivity and learning. In recent years, the terms IoT and IA have grown daily, making the scenario even more eye-catching, where one connects these devices to the Internet and promotes communication and the other gets interactivity between devices and users, respectively. Soon, the present work denominated Siscond, aims to implant computerized software that will facilitate the administration of a condominium using an application for smartphones compatible with the Android operating system. The objective is that the proposed system be a tool in the daily routine of managers and owners.